2014
DOI: 10.1021/cn5002254
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Modification of Alpha-Synuclein Serine 129 by Protein Kinase CK1 Requires Phosphorylation of Tyrosine 125 as a Priming Event

Abstract: S129-phosphorylated alpha-synuclein (α-syn) is abundantly found in Lewy-body inclusions of Parkinson's disease patients. Residues neighboring S129 include the α-syn tyrosine phosphorylation sites Y125, Y133, and Y136. Here, we use time-resolved NMR spectroscopy to delineate atomic resolution insights into the modification behaviors of different serine and tyrosine kinases targeting these sites and show that Y125 phosphorylation constitutes a necessary priming event for the efficient modification of S129 by CK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
4
56
0
1
Order By: Relevance
“…The physiological concentration of α-synuclein in neuronal synapses is estimated to be about 50 μM (27,28), a concentration of protein that can be studied by NMR spectroscopy (27,(29)(30)(31)(32). We therefore used this technique to probe potential interactions between α-synuclein and squalamine in the absence of lipids and to characterize the displacement of the protein from lipid membranes by squalamine, as suggested by the CD experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological concentration of α-synuclein in neuronal synapses is estimated to be about 50 μM (27,28), a concentration of protein that can be studied by NMR spectroscopy (27,(29)(30)(31)(32). We therefore used this technique to probe potential interactions between α-synuclein and squalamine in the absence of lipids and to characterize the displacement of the protein from lipid membranes by squalamine, as suggested by the CD experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It is often observed that phosphates are lost during extract preparation or during mass spectrometry processing and therefore, such sites are often not reliable. Such clusters often use one specific phosphorylation seed generated by a priming kinase, which is then recognized by secondary kinases that hyper-phosphorylated the cluster (Kosten et al, 2014). Using this stringent strategy, several phosphorylation sites that have been reported previously are not found in our data.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, C-terminal methionine sulfoxides impair Y125 phosphorylation by the major tyrosine kinase Fyn [83]. As phosphorylated Y125 primes the efficient modification of S129 by CK [129], reduction in Y125 phosphorylation is likely to also diminish modifications of S129. This would support the presence of an age- and disease-dependent decline in α-syn phosphorylation in models and patients of PD [127].…”
Section: Structure Changes To α-Synuclein That Induce Oligomerisationmentioning
confidence: 99%